Collaboration Model of Parents, Teacher and University Students in Supporting Learning from Home - Wael, Ahmad; Akib, Rizal; Paulina, Paulina; Ohorella, Hayat Marwan; Saputra, Dian (Universitas Muhammadiyah Gresik, 2024)
This research aims to develop a model of Teacher-Parent Collaboration and Student Assistance to support learning from home and strengthening post-pandemic learning. By using the Plom Development model, this research data was obtained through three stages of development, namely 1) Preliminary Research using interviews and field assessments as data collection instruments; 2) Development model with reference to preliminary research data; 3) Assessment to determine the validity, practicality and effectiveness of the model that has been developed using validity sheets, FGDs and student daily reports. The results of this research concluded that the collaborative model of teachers and parents with student assistance is applicable based on validity with an average value of 3.47 and Cronbach alpha 0.83 which can be interpreted as an acceptable model for implementation. In addition, this model is said to be effective in helping parents and students in the learning process from home by looking at an average value of 90% on aspects that are used to evaluate its effectiveness and being an effective model according to the responses of teachers and students in the implementation process.